Rekomendasi Fasilitas Berdasarkan Aktivitas pada Bantaran Tukad Petanu Kawasan Vihara Amurva Bhumi Desa Blahbatuh - I Putu Bagus Indra Darmawan; I Gusti Alit Gunadi (Nandur, 2023)
The river is a place and container as well as a network of water drainage from springs to estuaries bounded by demarcation lines. The Petanu River or Tukad Petanu is a river that crosses two regencies in Bali, its upstream is in Bangli Regency and its mouth is in Saba Beach, Gianyar Regency. Blahbatuh Villagerea of ??the Amurva Bhumi Vihara, Blahbatuh Village, is a natural river surrounded by dense forest and rocks with a variety of flora and fauna. Tukad Petanu in Blahbatuh Village is located on a low contour so that it is flanked by cliffs on the east and west sides. The Tukad Petanu area in the Amurva Bhumi Vihara area, precisely on the riverbank area, has various activities such as relaxing, sightseeing, recreation, meditation, yoga, and religious activities and is a historical area. The purpose of this research is to produce a facility recommendation that can accommodate visitor activities on the site and rearrange the physical condition of the banks to make them attractive, beautiful, and comfortable. The research method uses a survey method with data collection techniques field observations, interviews, and literature study which are then analyzed descriptively qualitatively through four systematic approaches, namely preparation, inventory, analysis, and synthesis. The results of this study indicate that the location of the site is quite strategic, has accessibility but lacks facilities to support the activities of site users. As for the addition and development of areas on the site, namely, resting areas, meditation areas, yoga areas, religious areas and food court areas along with circulation on the sites.